Kasper in the Glitter - Ridley, Philip (Penguin Group, 1995)
After his mother's brooch is stolen, Kasper leaves his home in the land of Nowhere and journeys to the land of Glitter and Gloom to get it back, confronting great dangers in a city ruled by a fierce orphan boy.
Keywords: Boys & Men; Juvenile Fiction